Altered angiogenesis in low birth weight individuals: a role for anti-angiogenic circulating factors. (February 2014) - Ligi, Isabelle; Simoncini, Stéphanie; Tellier, Edwige; Grandvuillemin, Isabelle; Marcelli, Maxime; Bikfalvi, Andreas; Buffat, Christophe; Dignat-George, Françoise; Anfosso, Francine; Simeoni, Umberto
Abstract Objective: Low birth weight (LBW) is a risk factor for hypertension at adulthood. Endothelial progenitor cells (EPCs) dysfunction has been characterized in LBW neonates. We hypothesized that changes in soluble, plasma pro- or anti-angiogenic factors are associated with EPCs dysfunction and impaired angiogenesis in LBW neonates. Method: Venous umbilical cord blood was collected from 42 normal, term neonates and 75 LBW neonates. Cord blood endothelial colony forming cells (ECFC) from control patients were cultured in the presence of 10% of serum obtained from both groups. Results: The proliferation and the migration of ECFC were significantly reduced when cultured with 10% of serum of LBW neonates compared to serum of control neonates. Matrigel invasion assay was not significantly altered. Umbilical vein plasma VEGF concentration was significantly reduced in LBW neonates while that of sVEGFR and PF4 were significantly higher. Addition of VEGF corrected the inhibitory effect of LBW serum on normal ECFC proliferation. Conclusions: Serum obtained from LBW babies contains factors that exhibit an antiangiogenic effect on ECFC proliferation and migration. VEGF/sVEGF/PF4 pathway seems to be involved in the EPCs dysfunction in LBW neonates.